Investigation on the Potential of Some N-phenylalkanehydrazides as Superoxide Anion Radical Scavengers and Glutathione Peroxidase Binders with ADME Prediction: Comparison with Vitamin C - Mouada, Hanane; Lanez, Touhami (Current Bioactive Compounds, 2025)
ObjectiveAn investigation on the antioxidant activity and ADME properties of some N-phenylalkanehydrazides (NPhs) in comparison with ascorbic acid was carried out.Materials and MethodsThe power of the compounds to scavenge the superoxide anion radical was examined using cyclic voltammetry. Furthermore, molecular docking was used to examine how NPhs bind to the antioxidant enzyme glutathione peroxidase (GPx). Finally, ADME properties were predicted using the SwissADME webserver.ResultsThe results showed that the studied compounds had significantly higher EC50 values than Vitamin C and displayed spontaneous binding with GPx with binding energy similar to ascorbic acid. Also, substantial values emerged from the predictive analysis of drug-likeness and bioavailability characteristics.DiscussionFirst, the EC50 of the compounds under study was determined by assessing the decrease in the anodic current peak intensity; this demonstrated significant radical scavenging activity. Next, the electrostatic way of binding with ROS radical and with antioxidant enzyme was disclosed by the binding free energies; however, the oxygen and nitrogen atoms in the compounds' structures might make many conventional hydrogen bonds with amino acids. Finally, NPh (a) followed all the rules for drug-likeness and bioavailability estimates, making it a promising moiety for synthesising new antioxidant chemicals.ConclusionThe current study is a hybrid of experimental and computational methods that complement each other perfectly.
Keywords: N-phenylalkanehydrazide